Implementation of Agile Methods in Production Planning and Control: The Role of Quality as Mediation towards Customer Satisfaction at Be Adab Coffee Shop Malang - Anton Ferry Ananda; Dedi Sukariyono; M Mastotok Illah; Lianita Widyaratna Kristanti; Handik Purwantoro (University of Merdeka Malang, 2025)
In the context of the coffee shop industry, it is important to understand how effective management methods can be applied to improve product and service quality. One approach that is gaining popularity is the Agile method, which was originally used in software development. These methods are now starting to be adapted in coffee shop production planning and control, enabling faster response to changing customer needs. Agile methods emphasize collaboration and iterative development, which is expected to improve product quality. However, the implementation of Agile methods is not easy. The process requires a deep understanding of the integration of various variables to achieve the desired goal. In this study, quality improvement serves as an important mediating variable, bridging the relationship between Agile methods and customer satisfaction. This research uses descriptive and associative approaches, where descriptive research describes the characteristics of respondents, while associative research tests the relationship between independent, mediating, and dependent variables. The research population includes all Be Adab Coffee Shop customers, with a sample size of 80 respondents. The data was analyzed using Smart PLS (Partial Least Squares) software. The results showed that the Agile method in planning has a positive effect on customer satisfaction, which means that the application of this method can make a good contribution. However, the effect of Agile methods on quality is insignificant, indicating that quality improvement cannot be relied upon as a direct result of applying these methods. In contrast, production control was shown to have a significant influence on quality. In addition, quality also has a positive impact on customer satisfaction. However, analysis of the effect of Agile methods in planning on customer satisfaction through quality showed no significant effect.